Psychosocial adjustment to breast cancer in women with conservative surgery vs mastectomy - Fernandes, Susana (2018)
The aim of this study was to examine psychosocial adjustment differences between breast cancer women who underwent a lumpectomy or mastectomy, predicting differences between the two groups. The participants were 74 Portuguese recently diagnosed breast cancer patients, recruited in the main Oncology Hospital of the North of Portugal. The study design is longitudinal with four-time points: before surgery (baseline); two weeks after surgery, during adjuvant treatments; and at the end of adjuvant treatment. The evaluated dimensions were emotional state, illness perception and illness functional limitations. We didn’t find differences for most of the variables, between the two groups. However, we find significant differences for comprehension (illness perception) and for leisure, sleep and psychosocial dimension (perceived functioning), with better adjustment for women who underwent mastectomy. These results are unexpected since conservation surgery aims to provide a more satisfying cosmetic outcome and survival rates equivalent to those of mastectomy, assuming a better psychosocial adjustment. The data suggest that the type of surgery doesn’t seem to predict the psychosocial adjustment. However, involving patients in choosing surgery type, whenever it is possible, can benefits a better understanding about the disease and the treatment, with more favourable repercussions on the emotional level and functionality.